Tinjauan Hukum Islam Terhadap Praktik Jual Beli Ikan Dalam Basket Dengan Akad Bai’ Al Muzayadah Di Tpi Klidang Lor Batang - Arzaq, Muhammad Rofiu; Hamid, Abdul; Mubarok, Riskon Mubarok (el hisbah Journal of Islamic Economic Law, 2022)
The practice of buying and selling fish using Baskets has become a community tradition at the Klidang Lor Batang Fish Auction Place in terms of buying and selling fish by auction using Baskets which in practice causes many problems, including differences in fish quality or mixed fish species in one basket. The purpose of the study was to describe the process of buying and selling fish in baskets with a Bai' Al Muzayadah contract at TPI klidang lor Batang and to know the review of Islamic law on the process of buying and selling fish in baskets at TPI klidang lor Batang. This type of research is a field research with descriptive analysis using a qualitative approach, the source of the data collected is primary data taken from direct locations both fish sellers (bakul), fishermen, TPI Ikan Klidang Lor Batang using the interview method, observation, documentation, and secondary data obtained from the literature. Based on the results of the study, the sale and purchase of fish in Basket with the Bai' AL Muzayadah contract is included in the 'Urf, which is a custom from the past. The practice of auctioning using baskets is allowed according to Islamic law (this transaction is categorized as permissible or permissible as long as there is no evidence that forbids it), the khiyar right is applied as a problem solver if you get fish that does not match the quality.